2017
DOI: 10.11648/j.ajns.20170604.14
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing Nurses While Participating in Continuing Professional Development: A Case of Western Kenya

Abstract: Background: The context of work for nurses is rapidly changing due to changes in care, innovative technologies, and emergence of new knowledge. Participation in Continuing Professional Development (CPD) in many countries in Africa remains low. Objective: The objective of the study was to explore the challenges facing Nurses while participating in CPD in Western Kenya. Methods: A descriptive cross-sectional study design was employed where 235 stratified and randomly selected nurses and four CPD Coordinators fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…However, this study documented 20.9% response of expensive training fees. This is in line with many studies (Schweitzer and Krassa, 2010;Fitzgerald et al, 2012;Katsikitis et al, 2013;Priscah et al, 2017), that also documented expensive training fee as their constraint to attending CPE. Some respondents in this current study suggested a reduction in cost of the program for all; while few said the cost should be reduced for just the retired nurses attending the program.…”
Section: Factors Influencing the Attendance Of Mcpdpsupporting
confidence: 89%
See 2 more Smart Citations
“…However, this study documented 20.9% response of expensive training fees. This is in line with many studies (Schweitzer and Krassa, 2010;Fitzgerald et al, 2012;Katsikitis et al, 2013;Priscah et al, 2017), that also documented expensive training fee as their constraint to attending CPE. Some respondents in this current study suggested a reduction in cost of the program for all; while few said the cost should be reduced for just the retired nurses attending the program.…”
Section: Factors Influencing the Attendance Of Mcpdpsupporting
confidence: 89%
“…A majority of the respondents (83.6%) chose Calabar as their preferred venue because of distance from home or work place, some of them indicated that they would like a change of venue, that is, they would prefer their workplace instead of the current venue as this will make it easier for the nurses to attend the program. This is supported by the work of Priscah et al (2017) that documented 27.2% nurses and midwives had distance as a challenge to attendance.…”
Section: Participants' Attendance Of Mcpdpmentioning
confidence: 76%
See 1 more Smart Citation